Pengaruh Kemampuan Matematika Terhadap Kemampuan Computational Thinking Pada Anak Usia Sekolah Dasar - Heri Kuswanto; Nani Rodiyanti; Yosi Nur Kholisho; Baiq Desi Dwi Arianti (Educatio, 2020)
Computational thinking ability need to be trained from an early age through the mathematics ability approach at the primary schools level. This study aims to analyze the effect of the analysis of mathematic ability to computational thinking abilities in primary schools age in sdn 2 sekarteja with 2 measurement variables including: computational thinking ability and math ability. This type of research is quantitative using descriptive methods. The population of this study was class V SDN 2 Sekarteja with a total of 30 students and the entire population becomes the sample, the type of research sample is saturated sample. Data collection techniques in this study used tests and documentation. The technique used to analyze the data was descriptive statistics. The results of this study indicated that, with n = 30 and a significant level of 5%, r table = 0.361, while the result rcount = 0.304. The results obtained were rcount â‰¤ rtabel, then Ha was rejected and Ho was accepted and the direction of the correlation was negative. It can be concluded that there was no significant relationship between the computational thinking abilities of elementary school age children in terms of mathematics abilities at SDN 2 Sekarteja